Improving communication between staff and disabled children in hospital wards: testing the feasibility of a training intervention developed through intervention mapping. Issue 1 (11th September 2017) - Gumm, Rebecca; Thomas, Eleanor; Lloyd, Claire; Hambly, Helen; Tomlinson, Richard; Logan, Stuart; Morris, Christopher
Abstract : Objective: To develop and test the feasibility of a novel parent-inspired training intervention for hospital ward staff to improve communication with disabled children when inpatients. Design: Training content and delivery strategies were informed by the iterative process of Intervention Mapping and developed in collaboration with parents of disabled children. Setting: UK University Hospital children's ward. Subjects: 80 medical, nursing, allied health professionals, clerical and housekeeping staff on a children's ward. Methods: Themes identified in previous qualitative research formed the basis of the training. Learning objectives included prioritising communication, cultivating empathy, improving knowledge and developing confidence. Participant feedback was used to refine content and delivery. Intervention documentation adheres to the Template for Intervention Description and Replication checklist. Results: Highlighting mandated National Health Service policies and involving the hospital Patient and Carer Experience Group facilitated management support for the training. Eighty staff participated in one of four 1-hour sessions. A paediatric registrar and nurse delivered sessions to mixed groups of staff. General feedback was very positive. The intervention, fully documented in a manual, includes videos of parent carers discussing hospital experiences, interactive tasks, small group discussion, personal reflection and intention planning. Generic and local resources were provided. Conclusion: It was feasible to deliver this new communication training to hospital ward staff and it was positively received. Early feedback was encouraging and indicates a commitment to behaviour change. Further piloting is required to establish the transferability of the intervention to other hospitals, followed by consideration of downstream markers to evaluate the effects on disabled children's inpatient experience. Organisational and cultural change is required to support individual behaviour change.